2016
DOI: 10.1515/amma-2015-0122
|View full text |Cite
|
Sign up to set email alerts
|

Rehabilitation in Patients with Anterior Cruciate Ligament Reconstruction Using Auxiliary Platelet-Rich Plasma Therapy

Abstract: Background: The main target after successful AnteriorCruciate Ligament (ACL) reconstruction is early rehabilitation. New options such as PRP (platelet rich plasma) may improve clinical outcomes.Objective: The aim of our study was to evaluate two consecutive series of patients who underwent ACL reconstruction, one with PRP treatment and one without it.Material and method: Two groups of consecutive patients underwent arthroscopic ACL reconstruction, using the SemiT and BPTB techniques. Postoperatively all patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“… 4 , 33 The IKDC and Lysholm scores in the PRP group at 3 months postoperatively were greater than those in the control group. Albu et al 1 also reported PRP therapy improving clinical scores, reducing pain and swelling at 3 months postoperatively, and speeding up the rehabilitation process. PRP improves joint homeostasis via the release of growth factors and bioactive molecules, reduces pain and knee swelling, and leads to improved knee function in the short- and medium-term postoperative periods.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“… 4 , 33 The IKDC and Lysholm scores in the PRP group at 3 months postoperatively were greater than those in the control group. Albu et al 1 also reported PRP therapy improving clinical scores, reducing pain and swelling at 3 months postoperatively, and speeding up the rehabilitation process. PRP improves joint homeostasis via the release of growth factors and bioactive molecules, reduces pain and knee swelling, and leads to improved knee function in the short- and medium-term postoperative periods.…”
Section: Discussionmentioning
confidence: 96%
“…PRP improves joint homeostasis via the release of growth factors and bioactive molecules, reduces pain and knee swelling, and leads to improved knee function in the short- and medium-term postoperative periods. 1 The medium- and long-term (6 and 12 months postoperatively) benefits of PRP in improving knee function were lacking, as proven by the IKDC and Lysholm scores. This finding might indicate that PRP has a short duration of action in the knee joint.…”
Section: Discussionmentioning
confidence: 99%